Analyzing the Pension System of the USSR - Aleksei V. Pudovkin (Vestnik MGIMO-Universiteta, 2015)
The article under the title "ANALYSIS OF THE PENSION SYSTEM OF THE USSR" deals with numerous aspects of development of the pension system of the former USSR. Since the improvement of the Russian pension system is presently high on the agenda, the author believes that analyzing the own historical experience in the first line is essential in order to create a sound and efficient pension system in Russia. The study presented in the article aims to execute an in-depth analysis of legislature on the soviet pension system with the view to recreate the architecture of the pension system of the USSR. In addition, the study also reflects on the official statistics for the said period to make a qualified and fundamental conclusion on the efficiency of the soviet pension system. The evolution of the pension system, based on statistical data evidently proves the efficiently of the soviet pension system. It is highly recommended that the positive aspects of the soviet pension system are taken into consideration when reforming the actual pension system of Russian Federation.